PENGALAMAN KOMUNIKASI PELANGGAN PABERIK UPNORMAL COFFEE ROASTERY BANDUNG - Desy Rahmawaty; Evi Novianti; Yustikasari Yustikasari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2022)
In the era of modern technology that is growing rapidly, it influences the formation of new innovations that attract the attention of young people. Like the innovation of processed coffee in a coffee shop that provides a variety of modern facilities, a varied menu and free internet network. Coffee shops can also be categorized as tourist attractions because they are visited by visitors during leisure time. Competition for coffee shops in the city of Bandung continues to increase, but Paberik Kopi Upnormal Coffee Roasters is an option for tourists, especially those who have an interest in coffee, this is because it provides an experience and a distinctive taste of coffee that has not been found in other coffee shops. The research method used is a phenomenological approach by Alfred Schutz and social construction theory by Peter L. Berger and Thomas Luckmann with a qualitative basis, and data collection techniques through interviews. The result of this research is that from a series of customer communication experiences, it is revealed that many types of communication experiences are felt by consumers, such as caring, openness, friendliness, indifference, and trust, but the communication experience that stands out the most and makes customers feel very comfortable is spending hours at Paberik Upnormal Coffee Roasters Bandung is an experience of open interpersonal communication between customers, and between customers and the manager of the Upnormal Coffee Roasters Bandung Keywords: Coffee Shop; Communication Experience; Customer Communication